GABAAreceptor dynamics and constructing GABAergic synapses - Tretter, Verena; Moss, Stephen J. (Frontiers in Molecular Neuroscience, 2008)
GABA A receptors are located on the majority of neurons in the central and peripheral nervous system, where they mediate important actions of the neurotransmitter gamma-aminobutyric acid. Early in development the trophic properties of GABA allow a healthy development of the nervous system. Most neurons have a high intracellular Cl- concentration early in live due to the late functional expression of the Cl-pump KCC2, therefore GABA has excitatory effects at this stage. Upon higher expression and activation of KCC2 GABA takes on its inhibitory effects while glutamate functions as the major excitatory neurotransmitter. Like all multisubunit membrane proteins the GABAA receptor is assembled in the ER and travels through the Golgi and remaining secretory pathway to the cell surface, where it mediates GABA actions either directly at the synapses or at extrasynaptic sites responding to ambient GABA to provide a basal tonic inhibitory state. In order to adapt to changing needs and information states, the GABAergic system is highly dynamic. That includes subtype specific trafficking to different locations in the cell, regulation of mobility by interaction with scaffold molecules, posttranslational modifications, that either directly affect channel function or the interaction with other proteins and finally the dynamic exchange between surface and intracellular receptor pools, that either prepare receptors for recycling to the surface or degradation. Here we give an overview of the current understanding of GABAAreceptor functional and molecular dynamics that play a major part in major part in maintaining the balance between excitation and inhibition and in changes in network activity.